Energy Efficiency as a Factor of Modernization in Era of the Industrial Revolution in 18th—19th Centuries in Europe (Sweden and England) - O. V. Kim (Научный диалог)
The question of the relationship between the processes of modernization and the development of energy in Sweden and England in modern times is considered. The author investigates the problem of regional features of early industrialization in these countries. A review of modern English-language historiography on this topic is carried out. The author’s development of a model of the synergetic relationship of energy consumption, energy efficiency and economic growth in the 18th—19th centuries is presented. The question is raised about the typological similarity of the processes of economic and technological development of Sweden and England in modern times in the context of the capitalist world-system. At the same time, it is shown how the specific natural and socio-economic conditions in these countries influenced the historically determined differences in the use of firewood, coal, steam engines. Particular attention is paid to such factors of Sweden’s development as the early nature of proto-industrialization processes and the country’s semi-peripheral position in the capitalist world-economy. The author reveals the logical connection between the key positions of England in the international system of production and exchange and the dynamic introduction of new energy sources in modern times. It was concluded that factors related to the position of a particular country in the system of center-peripheral relations were of decisive importance for economic growth and energy.